Description of Characteristics of Respondents of the Nutritional Recovery Program for Stunting Children - Palupi, Fitria Hayu; Dewi Rosita, Siskana (Institute Of Computer Science (IOCS), 2024)
The data analysis technique uses frequency distribution to determine the characteristics of respondents in the nutritional restoration program for stunted children. This research was carried out at the Grogol Health Center, Sukoharjo Regency. The population in this study is all mothers with toddlers aged 6-24 months at the Grogol Health Center, Sukoharjo Regency, there were 44 mothers. From the research results, it was found that 29 respondents were male (65.9%) and 15 female respondents (34.1%), 2 children (4.4%) who were underweight at birth, namely <2,500 grams, the average baby born has a normal body height, namely 48-52 cm, namely 37 children (84.1%) and there are 7 children (15.9%) with a body length less than normal. From the research results, it was found that 16 respondents were good weight (36,4%), 17 (38,6%) respondents underweight and 11 (25%) respondents very underweight, frequency distribution of Height for Age in the short category was 34 people (77.3%) and very short was 10 people (22.7%). The results of the study showed that the frequency distribution of weight for height in the good nutrition category was 27 responden (61,4%) , malnutrition was 16 (36,4%) respondens and risk of overnutrition was 1 responden (2,2%).